Covid-19 Association with Mucormycosis (CAM): An Experience from Single Hospital Based Study - Sana Salam, Miraj Ahmad, Shaista Alam, Sumiyya Ghulam, Muhammad Sheraz Qureshi, Aqsa Aslam,Sudhair Abbas Bangash, Aqsa Khalid, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to assess the outcomes experienced by patients diagnosed with mucormycosis linked with COVID-19 while they were hospitalized. Study Design: Retrospective study Place and Duration: This study was carried out at Sardar Begum Dental College from January, 2022 to June 2022. Methods: There were 215 patients of both genders had age 18-80 years were presented in this study. Included patients had confirmed coronavirus disease with symptoms of mucormycosis. Patients were provided informed written consent for detailed demographics. Clinical and laboratory outcomes among all cases were assessed. We used SPSS 22.0 to analyze all data. Results: There were majority males 165 (76.7%) and 50 (23.3%) females in this study. Mean age of the patients was 45.6±17.53 years and had mean BMI 26.13±8.17 kg/m2. We found that diabetes mellitus was the most common co morbidity in 140 (65.1%) cases, followed by hypertension in 85 (39.5%) cases. Frequency of rhino orbital mucormycosis was found in 110 (51.2%) cases, sinuses in 70 (32.6%) cases and cerebral in 35 (16.3%) cases. Majority of the cases were treated by steroid. Mean hospitalization was 16.8±7.67 days. Frequency of died patients was 28 (13.02%) because of CKD, renal dysfunction and orbital involvement. Conclusion: We concluded in this study that rhino-orbital involvement, CKD and renal dysfunction were a significantly risk factors for mortality among patients of COVID-19 with mucormycosis. Keywords: Mucormycosis, Covid-19, Mortality, Hospitalization, Steroids